Dietary and Weight Loss Benefits of a National Sugar-sweetened Beverage Health Warning Policy: A Microsimulation Analysis (OR28-02-19) - Grummon, Anna (Curr Dev Nutr, 2019)
OBJECTIVES: Overconsumption of sugar-sweetened beverages (SSBs) is a major contributor to obesity in the United States. To reduce SSB consumption, five U.S. states have proposed requiring front-of-package health warnings on SSBs. Randomized trials indicate that SSB health warnings reduce SSB purchases, but uncertainty remains regarding how these reductions translate into population-level dietary and health outcomes. We aimed to quantify the effects of a national SSB health warning policy on U.S. adults’ dietary behaviors and weight outcomes. METHODS: We developed and validated a Monte Carlo microsimulation model of dietary behaviors and bodyweight using dietary and anthropometric data from the National Health and Nutrition Examination Survey. Using estimates from existing literature, we simulated how an SSB health warning policy would affect SSB intake and, in turn, how changes in SSB intake would affect total energy intake. We then incorporated a validated model of weight change to translate changes in total energy intake into changes in weight over time. We used the model to simulate the impact of a national SSB health warning policy on SSB intake, total energy intake, body mass, and obesity among U.S. adults over a five-year period. Uncertainty analyses simulated scenarios when varying assumptions about three key model parameters: (1) the extent to which warnings would reduce SSB intake, (2) the degree of caloric compensation following a reduction in SSB intake, and (3) the extent to which warnings’ impact would increase or decrease over time. RESULTS: Implementing a national SSB health warning policy would reduce average SSB intake by 26.2 calories/day (95% uncertainty interval [UI] = −32.8, −19.4) and total energy intake by 32.4 calories/day (95% UI = −37.9, −26.7). These dietary changes would reduce average BMI by 0.6 kg/m(2) (95% UI = −0.7, −0.5) and obesity prevalence by 2.1 percentage points (95% UI = −3.2pp, −0.9pp). BMI reductions would be largest among adults who are Black or Hispanic, have low educational attainment, or have low income. Obesity reductions persist when assuming warning efficacy decreases over time and when using conservative estimates of warning impact or caloric compensation. CONCLUSIONS: Implementing a national SSB health warning policy could reduce SSB consumption, average BMI, and obesity among U.S. adults. FUNDING SOURCES: National Institutes of Health. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: